Use of complementary medicine and its association with SARS-CoV-2 vaccination during the COVID-19 pandemic: a longitudinal cohort study - Mayssan Nehme; Olivia Braillard; Pierre-Yves Rodondi; Idris Guessous (Swiss Medical Weekly)
AIMS OF THE STUDY: Patients are increasingly using and requesting complementary medicine therapies, especially during the COVID-19 pandemic. However, it remains unclear whether they use them in conjunction with conventional medicine or to replace vaccination or other approaches and whether they discuss them with their physicians as part of shared decision-making. This study aimed to evaluate the use and initiation of complementary medicine during the COVID-19 pandemic, focusing on the association between complementary medicine use and COVID-19 vaccination status.